Measurements of inclusive and differential fiducial cross-sections of t t ¯ $$ t\overline{t} $$ production with additional heavy-flavour jets in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector - The ATLAS collaboration; M. Aaboud; G. Aad; B. Abbott; O. Abdinov; B. Abeloos; D. K. Abhayasinghe; S. H. Abidi; O. S. AbouZeid; N. L. Abraham; H. Abramowicz; H. Abreu; et al. (Journal of High Energy Physics, 2019)
Abstract This paper presents measurements of t t ¯ $$ t\overline{t} $$ production in association with additional b-jets in pp collisions at the LHC at a centre-of-mass energy of 13 TeV. The data were recorded with the ATLAS detector and correspond to an integrated luminosity of 36.1 fb−1. Fiducial cross-section measurements are performed in the dilepton and lepton-plus-jets t t ¯ $$ t\overline{t} $$ decay channels. Results are presented at particle level in the form of inclusive cross-sections of t t ¯ $$ t\overline{t} $$ final states with three and four b-jets as well as differential cross-sections as a function of global event properties and properties of b-jet pairs. The measured inclusive fiducial cross-sections generally exceed the t t ¯ b b ¯ $$ t\overline{t}b\overline{b} $$ predictions from various next-to-leading-order matrix element calculations matched to a parton shower but are compatible within the total uncertainties. The experimental uncertainties are smaller than the uncertainties in the predictions. Comparisons of state-of-the-art theoretical predictions with the differential measurements are shown and good agreement with data is found for most of them.